EFEKTIVITAS PEMBELAJARAN BLENDED LEARNING PADA PENINGKATAN MENULIS “TEKS EXPOSISI” DI MA. AL-HUDA SUMBER NANGKA PAMEKASAN - ahmad ahmad; atnawi atnawi; Sitti Mukamilah (Fakultas Agama Islam Universitas Islam Madura, 2021)
The purpose of this study is (1) describing the improvement of text writing skills Exposition students of grade X MA Al-Huda Sumber Nangka Duko Timur Pamekasan, (2) describe the skills of writing text exposition with a blended learning system. This research is quantitative and qualitative research. Quantitative research is in the form of value analysis of the test results of writing exposition text. Qualitative research in the form of data analysis of nontest results through observations, questionnaires, interviews, and documentation. Based on the results of the test writing exposition text using blended learning learning system obtained results that the average grade X MA Al Huda students improved, it is evidenced by the results of research on pre-cycle students get an average grade score of 41.07. In cycle I the average grade of students increased to 63.75. From pre-cycle to cyclical I students' grades increased by a difference of 22.68. In cycle II learning students get an average grade of 67.70 and in cycle III the average grade of students increases to 80. From the learning of cycle I to cycle II increased with a difference of value of 3.95 while between cycle II to cycle III increased with a difference of value of 12.03. This proves that students' persuasive paragraph writing results improved from precyclical, cycle I, cycle II, and cycle III to good category.